The Correlation English Language Learning Motivation and Movie Watching Habits among EFL Students: Comparative Study: - - Aprilia Anggraini; Abdul Syahid; Fanny Hairunisa; Ananda, Rahmania (Universitas Negeri Medan, 2025)
This study looks into how watching English-language movies might influence the motivation of EFL students at IAIN Palangka Raya. Using a comparative cross-sectional design, the study involved 30 participants divided into two groups, those who frequently watch English-language movies and those who do not. Data were collected Using surveys and motivation scales. The results revealed a strong positive correlation between regular movie-watching and increased motivation, confidence, and cultural understanding. Key findings include significant differences in motivation levels, with frequent movie-watchers showing higher integrative and instrumental motivation. However, the impact on grammar and spontaneous speaking was less pronounced. The study concludes that English language films serve as an effective tool to boost learner motivation and engagement, emphasizing their potential role in modern language pedagogy. Limitations such as self-report bias and sample size are acknowledged, suggesting areas for future research.